Molecular characterization of EST microsatellites and analysis of population genetic structure in striped snakehead fish, Channa Striata / Sara Takalloo - Takalloo, Sara (2014)

(untitled)
The Striped snakehead fish, Channa striata is a freshwater air breathing fish species indigenous to Malaysia. It is locally known in Malaysia as Haruan. Channa striata is economically playing a major role in the aquaculture and fisheries industries. Channa striata is important especially as a food source in South East Asia. It has been broadly used for medical and pharmaceutical purposes due to its therapeutic and recuperative qualities. Among the many DNA marker systems available, EST microsatellites have a number of advantages due to its high level of transferability, high reproducibility, codominant inheritance and low cost for development compared to other molecular markers. The present study employed 20 EST microsatellites designed from RNA transcriptome sequencing. Out of the 15 loci which were able to be amplified, four loci were found to be polymorphic. The polymorphic EST-SSR loci were applied to investigate the level of genetic variation and differentiation of four geographical populations of C.striata. The populations involved in this study included Johor, Kedah, Pahang and Sarawak. The number of alleles per locus ranged from one to five. The highest value of heterozygosity was observed in Pahang population, while the lowest value corresponded to Kedah. No evidence of significant deviation from Hardy Weinberg Equilibrium was detected in all populations. There was no pattern on linkage among specific pairs of loci at all sites indicating no physical linkage is likely to be present among the loci analyzed. The value of population pair-wise Fst in this study indicates significant differentiation among populations. Kedah and Pahang are the most similar populations whereas Sarawak and Johor are the most different populations among them. iv Cross-species amplifications of C.striata primers were conducted on 10 species including Amblyrhynchicthy truncates, Barbichthys laevis, Barbonymus chwanenfeldii, Cirrhinus caudimaculatus, Hypsibarbus wetmorei, Osteochilus hasselti, Thynnichthys thynnoides, Pangasius nasutus, Hampala macrolepidota and Channa micropeltes. Out of the 10 species employed in cross-species amplification, Channa micropeltes was the only species in which the primers could work well. Among the 15 primers amplified in Channa striata, only 11 primers produced distinct and clear bands in Channa micropeltes. Seven out of these 11 primers could detect the same repeats indicating these primers were conserved in C.striata and C.micropeltes, which belong to the same family. This conservation of microsatellites can save time and cost in other Channidae family members since it is not necessary to develop microsatellite markers for each species.